2019
DOI: 10.3233/ais-190525
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the perceptibility of smartphone notifications in smart lighting spaces

Abstract: In smart spaces with connected smart lighting, there is an opportunity to deliver smartphone notifications using peripheral light, along with using standard smartphone modalities such as sound, vibration and LEDs, in order to help a user perceive them without constantly monitoring their mobile device. In this paper, we examine the effectiveness of on-device and extra-device modalities through smart lighting. We address a gap in literature by establishing a foundation that explains the role of modalities with w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…We believe that the primary task (TED talk, quiz) attracted the attention so much that participants showed a natural reaction to the vibration of the smartwatch and therefore they first checked the display on the smartwatch. This confirms the obtrusive character of the vibration channel [11,17] and may be too obtrusive for the meeting room context with ambient lighting as it seems to have a rather dominant effect on participants' attention and may prevent the ambient lighting from quickly moving to the center of attention.…”
Section: Resultsmentioning
confidence: 56%
See 3 more Smart Citations
“…We believe that the primary task (TED talk, quiz) attracted the attention so much that participants showed a natural reaction to the vibration of the smartwatch and therefore they first checked the display on the smartwatch. This confirms the obtrusive character of the vibration channel [11,17] and may be too obtrusive for the meeting room context with ambient lighting as it seems to have a rather dominant effect on participants' attention and may prevent the ambient lighting from quickly moving to the center of attention.…”
Section: Resultsmentioning
confidence: 56%
“…That is, the brightness of the LED stripes faded repeatedly with a period of 3.5 seconds from bright to darker and then back to bright again, whereby the LED stripes in the darkest state still shined with low intensity. According to [11,15], too rapid changes in parameters, such as brightness, have been shown to be more distracting than gradual changes, which would interrupt or disturb processes or the concentration of participants in meetings. Therefore, we chose a noticeably different type of notification for the second condition, whereby the slow pulsing greatly alleviated the distracting character.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Analysing the perceptibility of LED notifications, [27] concluded that only a fraction of users noticed LED blinks even when the phone was lying on the table. Going a step forward, [28] determined that LED notifications are easy to be missed. Thus, a smartphone blinking is not considered suspicious at all, though this study considers blinking features for better stealthiness.…”
Section: B User Modelmentioning
confidence: 99%